Impact of Loads and Photovoltaic Uncertainties on Cascaded Failure in Transmission Networks of Future Power Grids - Wasseem Al-Rousan; Rafat Aljarrah; Mazaher Karimi; Firas Obeidat; Qusay Salem (IEEE Access)
The increase investment of renewable energy resources (RESs) into power systems, such as solar photovoltaics (PVs), introduces additional uncertainty in transmission line loading. This uncertainty adds challenges to cascading failure analyses of power systems especially in future power scenarios of high penetration of RESs. In this paper, cascaded failures of power systems caused by the sequence tripping of transmission lines in the presence of RESs (mainly PV systems) is analyzed. By studying the lost power and the line failure probability, the potential impact of integrating more RESs on cascaded failures is investigated. In this regard, the uncertainties of RESs are examined by adding PV systems probability distribution function that reflects the solar irradiance for a typical day.A transmission-boosting approach is proposed in this paper to minimize the impact of failure risk to mitigate the possibility of the cascaded failure caused by the increased penetration of RESs. This paper presents a systematic approach to mitigate the risk of cascading failures via reconducting of transmission lines. Simulation studies for different penetration scenarios of PV systems have been carried out to test the impact on the cascaded failure and to validate the proposed transmission-boosting approach. The results in this paper imply that the increase in penetration of PV systems in the power grid would increase the potential of both cascaded failure risk and occurrence. In addition, the results have shown the efficacy of the proposed transmission-boosting approach in minimizing the cascaded failure risk when implemented. The findings have been validated using the modified version of the IEEE 39-bus test system modeled and simulated in Matlab.